2019
DOI: 10.1007/s00220-019-03547-9
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Decay for the Asymptotic Geometry of the Hitchin Metric

Abstract: We consider Hitchin's hyperkähler metric g L 2 on the SU(n)-Hitchin moduli space over a compact Riemann surface. We prove that the difference between the metric g L 2 and a simpler "semiflat" hyperkähler metric g sf is exponentially-decaying along generic rays in the Hitchin moduli space, as conjectured by Gaiotto-Moore-Neitzke. 1 arXiv:1810.01554v2 [math.DG] 29 May 2019 2 h 0z dz. (Note that because C is Kähler, the Hodge star on 1-forms depends only on the conformal class of the metric g C .)An infinitesimal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…This is accomplished with careful attention to the rate of exponential decay, but unfortunately they miss the conjectured sharp numerical value of this rate by a factor of 2. Their result has successfully been extended to the entire space M ′ , including non-horizontal directions and the region off of the Hitchin section, in the very recent preprint [Fr18] by Laura Fredrickson.…”
Section: Introductionmentioning
confidence: 91%
“…This is accomplished with careful attention to the rate of exponential decay, but unfortunately they miss the conjectured sharp numerical value of this rate by a factor of 2. Their result has successfully been extended to the entire space M ′ , including non-horizontal directions and the region off of the Hitchin section, in the very recent preprint [Fr18] by Laura Fredrickson.…”
Section: Introductionmentioning
confidence: 91%
“…For cyclic Higgs bundles, this was improved to pointwise monotonicity in [10,11]. These observations are intertwined with the "Hitchin WKB problem" [16,25,27,21,26,14,15,12] in the nonabelian Hodge theory of X, asking about the behaviour of harmonic metrics, harmonic maps, and their corresponding flat connections as t goes to infinity in (E, tΦ). Again, this problem has been resolved for cyclic Higgs bundles in the Hitchin section [8].…”
Section: Introductionmentioning
confidence: 96%
“…In these notes, we give an introduction to the hyperkähler geometry of the Hitchin moduli space, focusing on the geometry of the ends of the Hitchin moduli space. In the last section (Section 4), we briefly survey some recent developments in the description of the asymptotic geometry of M. We start with Gaiotto-Moore-Neitzke's conjectural description in [17,18] and survey recent progress in [12,13,14,27,28]. We take a meandering path through more classical geometric results to get there.…”
mentioning
confidence: 99%
“…Mazzeo-Swoboda-Weiss-Witt [28] have shown that along a generic ray g M −g sf decays polynomially in t. Dumas-Neitzke [12] have shown that -restricted to the Hitchin section -g M − g sf decays exponentially in t like O e −2M t . The author has shown that along a ray in M SU(2) g M − g sf decays exponentially in t [13]. However, the constant of exponential decay is not sharp.…”
mentioning
confidence: 99%
See 1 more Smart Citation